A Method of Managing Electrical Injury Around Oral Cavity - Bhattacharya, V.; Sinha, J. K.; Tripathi, F. M. (Indian Journal of Plastic Surgery, 1982)
This case report illustrates one of the methods for the management of deformities caused by electrical contact around mouth. The lip was advanzad for the reconstruction of oral sphincter. The chin defect was covered by a cervical transposition cum rotation flap.